1994
DOI: 10.1007/bf00188708
|View full text |Cite
|
Sign up to set email alerts
|

Texture relationships and interface structure in Ag-sheathed Bi(Pb)-Sr-Ca-Cu-O superconducting tapes

Abstract: We have studied the phase composition, alignment, and bonding at the Ag/Bi-Sr-Ca-Cu-O (BSCCO) interface for silver-sheathed tapes of both the 2212 and 2223 compositions which have been processed under different conditions. Strong texturing of the (001) planes of the BSCCO phases parallel to the Ag interface was seen, regardless of the Ag orientation. Short facets of non-(001) BSCCO planes accommodate local misalignments between the Ag and the (001) planes of the BSCCO phases. Whether the 2212 composites are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…We believe that the c-axis transport characteristics arise from the need to intermittently transfer the current from the strongly conducting a-b planes to the poorly conducting c-axis, when the continuous, good a-b plane current path is blocked 20,21 . We have observed the same ohmic characteristics of Fig.…”
mentioning
confidence: 99%
“…We believe that the c-axis transport characteristics arise from the need to intermittently transfer the current from the strongly conducting a-b planes to the poorly conducting c-axis, when the continuous, good a-b plane current path is blocked 20,21 . We have observed the same ohmic characteristics of Fig.…”
mentioning
confidence: 99%
“…Fine filaments are desired to improve the current density since most of the supercurrent flow occurs close to the silver-superconductor interface. 6 In order to address these issues, an alternative to the solid-state powder precursor-namely, chemically derived powder-is being examined. The advantages of chemically derived powders include a high degree of homogeneity; better batch-to-batch reproducibility, especially in the overall powder composition; and smaller size distribution of powder particles.…”
Section: Bi-2223 Powder-in-tube Superconductorsmentioning
confidence: 99%
“…The powder-in-tube (PIT) process for the Ag-clad Bi-2223 system is a promising and industrially scalable technique for fabricating long-length superconductors. Although considerable progress has been made recently in fabricating PIT tapes and enhancing their critical-current density (J c ) values, the complexities involved in obtaining phase purity, crystal orientation, good intergranular connectivity and sufficient mechanical strength in a brittle multicomponent oxide have long impeded the successful commercialization of high-T c superconductors [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial effort is now focused on addressing this limitation. Several research groups have reported that in Ag-clad Bi-2223 tapes the supercurrent is transported through a thin region at the silver-superconductor interface [4][5][6][7][10][11][12][13][14]. The high-current superconducting layers are generally ≈2-3 µm thick and have been shown to support a transport current with J c > 10 5 A cm −2 at 77 K and zero applied field [4,15].…”
Section: Introductionmentioning
confidence: 99%